1991
DOI: 10.1007/bf01665308
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of patients with parathyroid carcinoma: An update and review

Abstract: Parathyroid carcinoma is a rare cause of primary hyperparathyroidism. However, to our best knowledge, at least 163 cases of functioning parathyroid carcinoma appeared in the English literature from 1981 to 1989. We summarize the available information obtained from the reports of those patients and compare it with previous descriptions of the disease. The etiology of parathyroid carcinoma is usually obscure, but the possibility of a radiation-induced malignant change in the parathyroid gland became evident in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
1
34

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(232 citation statements)
references
References 58 publications
(96 reference statements)
8
189
1
34
Order By: Relevance
“…In contrast to previous reports stating that parathyroid carcinoma was found in only 0.3-3.0% of pHPT cases in a Caucasian population [16][17][18][19], our study revealed a very high incidence of parathyroid carcinoma in Japanese patients. Obara and Fujimoto also reported that parathyroid carcinoma was more common in Japanese patients with pHPT [19]. They found parathyroid carcinoma in 4.6% of patients with pHPT.…”
Section: Methodscontrasting
confidence: 99%
“…In contrast to previous reports stating that parathyroid carcinoma was found in only 0.3-3.0% of pHPT cases in a Caucasian population [16][17][18][19], our study revealed a very high incidence of parathyroid carcinoma in Japanese patients. Obara and Fujimoto also reported that parathyroid carcinoma was more common in Japanese patients with pHPT [19]. They found parathyroid carcinoma in 4.6% of patients with pHPT.…”
Section: Methodscontrasting
confidence: 99%
“…Although parathyroid carcinoma (PC) is an uncommon finding, accounting for only 1-2% of patients with primary hyperparathyroidism (PHPT); a relatively higher incidence has been reported in Italy and Japan, in consistent with our study (28,29). Another possible etiology that can explain the higher incidence may be the fact that our hospital is a tertiary center receiving more complicated cases who are candidates for surgery.…”
Section: Discussionsupporting
confidence: 86%
“…The usual TNM staging system cannot be applied to this disease for two reasons. First, parathyroid carcinoma is not a disease that frequently metastasizes to lymph nodes, 8,10 and, second, tumor size does not seem to play a role in prognosis. 10 In our series, we chose to use staging criteria on the basis of clinical and histopathologic invasiveness of the tumor.…”
Section: Discussionmentioning
confidence: 99%